A STABILITY STUDY OF OMEPRAZOLE DILUTED IN SODIUM CHLORIDE FOR INTRAVENOUS INFUSION AND DISCUSSION REGARDING CURRENT PRACTICE IN UK PAEDIATRIC INTENSIVE CARE UNITS. Issue 9 (17th August 2016) - Morris, Stephen
Abstract : Background: Omeprazole by intravenous infusion is occasionally warranted in children during episodes of acute upper gastro-intestinal bleeding. This is to ensure the continued suppression of stomach acid to reduce the of risk of re-bleeding. Current practice in UK paediatric intensive care units varies, but the use of 160 mg/1.73 m 3 over 24 hour has previously been reported.1 This is commonly prepared as a 0.8 mg/ml solution changed either at 12 or 24 hrs after preparation depending on reference source used.2 – 3 The current practice of using a 0.8 mg/ml (40 mg/50 ml) is off label and not endorsed by manufacturers who recommend a maximum concentration of 0.4 mg/ml3 . Following these recommendations would lead to a fluid load of 400 ml/1.73 m 2 which is likely to be significant. Excess fluid intake has been shown to correlate with increased oxygenation index and increased PICU stay.4 The aim of this study is to provide stability data for using 0.8 mg/ml for intravenous infusion which is currently in widespread despite use a lack of published lack of data in this area. Methods: A series of analytical techniques were performed to assess physical and chemical stability. Test solutions were prepared by reconstituting Losec® (Omeprazole) 40 mg powder for infusion and diluting to either 50 ml or 100 ml in 0.9% sodium chloride. Reverse phase HPLC analysis was conducted at 0 hrs, 10 hrs and 24 hrs. Particle size was assessed using a zeta potential analyser at 15-minute intervals over 60 minutes. Results: At both 40 mg/50 mL and 40 mg/100 mL the concentration of omeprazole remained at 101% and 100% after 10 hrs respectively. However significant degradation was seen at 24 hrs as concentrations reduced to 60% and 55% respectively. The difference between degradation after 10 hrs was not statistically significant when samples were compared using paired t-test with t(1)=1.25, p=0.427. Particle size analysis showed no statistical different between amount of particles in samples taken from all time points for both solutions with unpaired t-test t(8)=0.5625, p=0.59. Discussion: Our study confirmed the current manufacturers recommendations that omeprazole at 0.4 mg/ml is stable in sodium chloride for 12 hrs only. We also showed that a more concentrated solution of 0.8 mg/ml had the same degradation profile as 0.4 mg/ml. We recommend that when continuous intravenous infusions of omeprazole is required, that it is administered by preparing 0.8 mg/ml in NaCl 0.9% and changed every 12 hrs.